Transfer Possibilities of a Deep Learning System from Medicine into Aviation - Samim Ahmad Multaheb (2019)
This thesis deals with the possibilities to learn from medicine how to apply deep learning technology in aviation. From the basic understanding of artificial intelligence (AI), machine learning, deep learning, and the precise distinction between these fields, to the advantages and limitations of deep learning, this thesis aims to give an introduction to the complex field of AI and deep learning. The theory is underlined with various deep learning use cases in both industries. The transfer bridge between two similar use cases from medicine and aviation, genomic exon detection and lightning strike damage detection is built methodologically to investigate possible profits of the transfer from academia to the private sector.